Reuse and exchange of compound digital objects on the Web: the OAIORE project - Orduña-Malea, Enrique (Anuario ThinkEPI, 2009)
The reuse and exchange of compound digital web resources offers new possibilities to create and describe collections of objects, regardless of their location, thereby facilitating new academic workflows. This paper is focused on the OAI-ORE project, the goals of which are based on the identification and description of aggregations of web resources and their interrelationships.
Keywords: OAI-ORE; Compound digital objects; Aggregated resources; Resource maps; Dataset.